If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 100 = -4(3v + -1) Reorder the terms: 100 = -4(-1 + 3v) 100 = (-1 * -4 + 3v * -4) 100 = (4 + -12v) Solving 100 = 4 + -12v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '12v' to each side of the equation. 100 + 12v = 4 + -12v + 12v Combine like terms: -12v + 12v = 0 100 + 12v = 4 + 0 100 + 12v = 4 Add '-100' to each side of the equation. 100 + -100 + 12v = 4 + -100 Combine like terms: 100 + -100 = 0 0 + 12v = 4 + -100 12v = 4 + -100 Combine like terms: 4 + -100 = -96 12v = -96 Divide each side by '12'. v = -8 Simplifying v = -8
| 6Sin^2(X)-Sin(X)-2=0 | | 5(4m-8)=-140 | | -8(-3k+5)=128 | | 174=-6(1-5r) | | 3m-1=4 | | tan(62)=x/15 | | 1=3t-2 | | 9q-2=-2 | | 9x+8=89x | | 56=8z | | logk=20 | | 35=7s | | 0.5x=12x | | 24=3v | | 2+8m=18m | | 18=9c | | 8n+50=109 | | 24=2B+g | | (0,3/0,01)*2*((0,2*1,9*10^3)/(N*0,3*0,9))^(1/3)*(12/6)^(0,14) | | 4a^2-20a-24=0 | | 3x+5y+2z=2 | | -p^2+p+20=0 | | 4e=24 | | -3p-(-3)/-6=-12 | | 36=9m | | 7x-11/5x-2=2x-9/5x-2 | | 2x=9-5x+32 | | t+8=4t+5 | | 8z-6=7z | | ((x^2-ax-8)/(x-a))=0 | | 8(x-8)=4(x+4) | | (3x-4)(2x+5)=20 |